1989
DOI: 10.1093/nar/17.20.8364
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a variant form of the human estrogen receptor with an amino acid replacement

Abstract: EMBL accession no. X15056Estrogen receptor (ER) is a ligand-dependent transcriptional regulator. ER protein has several functionally distinct regions, including a DNA-binding domain in its

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

1991
1991
2006
2006

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(14 citation statements)
references
References 7 publications
0
14
0
Order By: Relevance
“…Some portion of the genetic risk factors for MD in women might reflect the sensitivity to the depressogenic effect of menstrual and/or pregnancy-related hormonal changes, [35][36] mediated, for example, by variation in the estrogen receptor. 37 Such genetic risk factors, while expressed in women, would be largely dormant in men. In accord with this hypothesis, we recently found that genetic risk factors for premenstrual symptoms accounted for ∼17% of the genetic risk factors for lifetime MD in female twins.…”
Section: Genetic Risk Factors For MD In Men and Women: Same Or Differmentioning
confidence: 99%
“…Some portion of the genetic risk factors for MD in women might reflect the sensitivity to the depressogenic effect of menstrual and/or pregnancy-related hormonal changes, [35][36] mediated, for example, by variation in the estrogen receptor. 37 Such genetic risk factors, while expressed in women, would be largely dormant in men. In accord with this hypothesis, we recently found that genetic risk factors for premenstrual symptoms accounted for ∼17% of the genetic risk factors for lifetime MD in female twins.…”
Section: Genetic Risk Factors For MD In Men and Women: Same Or Differmentioning
confidence: 99%
“…When considering all the published data, it is quite possible that a single gene at 6q27 could have relevance to the development and progression of a wide variety of tumour types. (McGuire et al, 1992) and an Ala-Val substitution was recognised by an RNase protection assay (Garcia et al, 1989). Some of these variants have functional significance, acting in some cases as a dominant positive receptor, i.e.…”
Section: Loh On Chromosome 6qmentioning
confidence: 99%
“…Polymorphisms of CYP1A1 MspI, ERa PvuII, and ERa XbaI are the possible risk factors implicated in the initiation and development of the breast cancer through estrogen tumorigenesis pathway (3)(4)(5)(6)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25). Hence, we examined whether polymorphisms of these two genes that are related to estrogen metabolism and its effect increases the risk of breast cancer among Chinese women.…”
Section: Introductionmentioning
confidence: 99%